THE PSYCHEDELIC RENAISSANCE: A SYSTEMATIC REVIEW OF PSILOCYBIN AND LSD IN THE TREATMENT OF PSYCHIATRIC DISORDERS - Jakub Klepacz,; Radosław Swędrak,; Marzena Swojnóg,; Zuzanna Dobrakowska, (International Journal of Innovative Technologies in Social Science, 2026)
The escalating global burden of mental health disorders, coupled with the stagnation of innovation in traditional monoaminergic pharmacotherapy (e.g., SSRIs), has precipitated a critical need for novel therapeutic paradigms. This article presents a comprehensive systematic review of the so-called "Psychedelic Renaissance," focusing on the clinical resurgence of classical serotonergic hallucinogens: psilocybin and Lysergic Acid Diethylamide (LSD). The review adopts an interdisciplinary structure to evaluate the efficacy, safety, and societal implications of these compounds. Firstly, the paper traces the historical evolution of psychedelics from indigenous sacramental use, through the research proliferation of the 1950s, to the prohibitive legislation of the late 20th century. Secondly, it delineates the neurobiological mechanisms of action, specifically 5-HT2A receptor agonism and the disintegration of the Default Mode Network (DMN), which correlates with the alleviation of rigid cognitive patterns in depression and anxiety. Thirdly, the review synthesizes data from contemporary clinical trials demonstrating significant therapeutic potential in Treatment-Resistant Depression (TRD), end-of-life existential distress, and substance use disorders. Unlike standard pharmacological reviews, this paper also analyzes the distinct psychotherapeutic framework ("set and setting"), integration processes, and socio-economic factors, including cost-effectiveness and access equity. The findings suggest that psychedelic-assisted therapy represents a transformative shift from chronic symptom management to rapid, episodic curative interventions, provided that regulatory and ethical challenges are adequately addressed.